Multilevel approach to competitiveness in the global tourism industry - Teixeira, Sérgio Jesus, 1984-; Ferreira, João J. M. (Advances in hospitality, tourism, and the services industry book series., 2020)
"This book examines the issues, challenges, opportunities, and trends in the global tourism industry"--